Reactive separation of organic mixtures using functionalized Zeolite Membranes. - Bhatia, Subhash; Ahmad, Abdul Latif; Abdullah, Ahmad Zuhairi (Universiti Sains Malaysia, 2008)

(untitled)
Systematic investigation of acid functionalized silicalite-l (MFI type zeolite) membrane synthesis has been conducted in this project.